(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Sergey V. Mukhin (Moscow, Russian Federation) The article is focused on the study of the linguistic unit land / lond as functioning in the toponymic system of Old English. The contextual examples of land-toponyms are drawn from the Anglo-Saxon Chronicle. There is an attempt to reveal the role of the component land / lond in forming Old English appelative and onomastic toponyms. The texts of the five versions of the Chronicle have been processed in order to pick out all the derived and compound toponyms with the land component and group them according to the semantic and geographic criteria. The component land / lond proves to be an effective tool of forming toponyms. The appelative toponyms tend to be terminological and fall into the groups of geographic, political, economic and military terms, whereas onomastic lexemes are mainly used to name the medieval kingdoms, regions of Britain and continental Europe and islands. Key words: component land / lond, Old English, toponymy, Anglo-Saxon Chronicle, word-building. DOI 10.23683/1995-0640-2019-4-47-55